The Influence of Environmental and Cognitive Factors on the Entrepreneurial Intentions of Female Students in the STEM Field - Eva M. Sánchez-Teba; Guillermo Bermúdez-González; María-Dolores Benítez-Márquez (SAGE Open)
By merging the theory of planned behavior and social cognitive theory, in this study an attempt is made to identify the cognitive and environmental factors that influence the entrepreneurial intentions of female university science, technology, engineering and mathematics (STEM) students in Andalusia, Spain. The data were obtained from a cross-sectional survey, carried out in 2022, of female students studying for a degree in product engineering. A variance-based structural equation model was estimated by applying partial least squares. The results showed that the cognitive factors of attitude toward behavior and perceived behavioral control positively influenced female STEM students’ entrepreneurial intentions, while subjective norms do not. Of the environmental factors, only closer valuation positively impacted on their predisposition to become entrepreneurs. Attitude toward behavior is the key driving factor of entrepreneurship intentions among female engineering students. For predisposition toward entrepreneurship to provide more advantages than disadvantages, several issues must be addressed. Students who have a close circle of family and friends who believe in entrepreneurship have a stronger disposition toward self-employment, have greater confidence in their ability to be successful and receive greater social approval. The image of entrepreneurship must be improved, thereby promoting entrepreneurial intentions within educational contexts, not only among university students but, also, among young people in general. Female engineering students do not need the approval of their family and friends to want to start a business. Future research might undertake longitudinal and cross-cultural analyses.